2011
DOI: 10.2139/ssrn.1892274
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Growth in Africa: The Broken Link

Abstract: ABSTRACT. Utilizing the latest panel cointegration methods we provide new empirical evidence from 18 countries that suggests that the link between finance and growth in SubSaharan Africa is 'broken'. Specifically, our findings show that banking system development in this region follows economic growth. They also indicate that there is no link between bank credit and economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 18 publications
3
34
4
Order By: Relevance
“…Private seems to be the best financial development proxy because all the growth proxies are significant at 1% whereas gk is significant at 5% for lly (as dependent variable) and not significant for privy (as dependent variable). This observation is contrary to the findings of Demetriades & James (2011) who observed that there is no long run relationship when credit is the proxy for financial development. From the foregoing, we observe that the regression results obtained with two different analytical approaches are not different from each other.…”
Section: Wwwmacrothinkorg/ber Represents Inflation Of the I-thcountcontrasting
confidence: 99%
See 3 more Smart Citations
“…Private seems to be the best financial development proxy because all the growth proxies are significant at 1% whereas gk is significant at 5% for lly (as dependent variable) and not significant for privy (as dependent variable). This observation is contrary to the findings of Demetriades & James (2011) who observed that there is no long run relationship when credit is the proxy for financial development. From the foregoing, we observe that the regression results obtained with two different analytical approaches are not different from each other.…”
Section: Wwwmacrothinkorg/ber Represents Inflation Of the I-thcountcontrasting
confidence: 99%
“…This aspect of the study does not form part of the King and Levine (1993) study hence difficult to make any comparison. However, it contrasts the findings of Demetriades & James (2011) who find that only liquid liabilities follow (but not lead) growth and Kumar (2011). However it lends support to the findings of Estrada et al (2010); Akinlo & Egbetunde (2010) and Johannes (2011).…”
Section: Key: Same As Table 3 Abovecontrasting
confidence: 89%
See 2 more Smart Citations
“…Financial development improves consumption levels by enabling households to spend more money by credit financing. In this context financial development increases the possi-1 For recent counterevidence see Demetriades and James (2011).…”
Section: Introductionmentioning
confidence: 99%